Countering Online Drug Trafficking Networks through the Application of Cybersecurity Technology: A Case Study of the Labuhanbatu Resort Police - Andi Fahri Hasibuan; Riza Zarzani; Henry Aspan (PT. Sinergi Legal Publisher, 2025)
This research analyzes the characteristics of pretrial rulings that annul the suspect designation by the Corruption Eradication Commission (KPK) and its implications for the performance and independence of the institution. Regulatory changes through Law No. 10 of 2015 and Law no. 19 of 2019 pose challenges related to the principles of justice, legal certainty, and the integrity of legal processes. Pretrial decisions that invalidate the suspect designation emphasize the importance of adherence to legal procedures and the protection of human rights in the enforcement of anti-corruption laws. Judicial oversight through pretrial is necessary to maintain a balance between KPK's independence and the protection of individual rights. The findings underscore the need for clearer and more accountable regulations to ensure effective and fair anti-corruption efforts